Associations between renal duplex parameters and adverse cardiovascular events in the elderly: a prospective cohort study. - Pearce, Jeffrey D; Craven, Timothy E; Edwards, Matthew S; Corriere, Matthew A; Crutchley, Teresa A; Fleming, Shawn H; Hansen, Kimberley J (Am J Kidney Dis, 2010)
BACKGROUND: Atherosclerotic renovascular disease is associated with an increased risk of cardiovascular disease (CVD) events. This study examines associations between Doppler-derived parameters from the renal artery and renal parenchyma and all-cause mortality and fatal and nonfatal CVD events in a cohort of elderly Americans. STUDY DESIGN: Cohort study. SETTING: A subset of participants from the Cardiovascular Health Study (CHS). Through an ancillary study, 870 (70% recruitment) Forsyth County, NC, CHS participants consented to undergo renal duplex sonography to define the prevalence of renovascular disease in the elderly, resulting in 726 (36% men; mean age, 77 years) technically adequate complete studies included in this investigation. PREDICTOR: Renal duplex sonography-derived Doppler signals from the main renal arteries and renal parenchyma. Spectral analysis from Doppler-shifted frequencies and angle of insonation were used to estimate renal artery peak systolic and end diastolic velocity (both in meters per second). Color Doppler was used to identify the corticomedullary junction. Using a 3-mm Doppler sample, the parenchymal peak systolic and end diastolic frequency shift (both in kilohertz) were obtained. Resistive index was calculated as (1 - [end diastolic frequency shift/peak systolic frequency shift]) using Doppler samples from the hilar arteries of the left or right kidney with the higher main renal artery peak systolic velocity. OUTCOMES & MEASUREMENTS: Proportional hazard regression analysis was used to determine associations between renal duplex sonography-derived Doppler signals and CVD events and all-cause mortality adjusted for accepted cardiovascular risk factors. Index CVD outcomes were defined as coronary events (angina, myocardial infarction, and coronary artery bypass grafting/percutaneous coronary intervention), cerebrovascular events (stroke or transient ischemic attack), and any CVD event (angina, congestive heart failure, myocardial infarction, stroke, transient ischemic attack, and coronary artery bypass grafting [CABG]/percutaneous transluminal coronary intervention [PTCI]). RESULTS: During follow-up, 221 deaths (31%), 229 CVD events (32%), 122 coronary events (17%), and 92 cerebrovascular events (13%) were observed. Renal duplex sonography-derived Doppler signals from the renal parenchyma were associated independently with all-cause mortality and CVD outcomes. In particular, increased parenchymal end diastolic frequency shift was associated significantly with any CVD event (HR, 0.73; 95% CI, 0.62-0.87; P < 0.001). Marginally significant associations were observed between increases in parenchymal end diastolic frequency shift and decreased risk of death (HR, 0.86; 95% CI, 0.73-1.00; P = 0.06) and decreased risk of cerebrovascular events (HR, 0.78; 95% CI, 0.61-1.01; P = 0.06). Parenchymal end diastolic frequency shift was not significantly predictive of coronary events (HR, 0.84; 95% CI, 0.67-1.06; P = 0.1). LIMITATIONS: CHS participants showed a "healthy cohort" effect that may underestimate the rate of CVD events in the general population. CONCLUSION: Renal duplex sonographic Doppler signals from the renal parenchyma showed significant associations with subsequent CVD events after controlling for other significant risk factors. In particular, a standard deviation increase in parenchymal end diastolic frequency shift was associated with 27% risk reduction in any CVD event.
Keywords: Aged; Cardiovascular Diseases; Cohort Studies; Female; Humans; Kidney Diseases; Male; Renal Artery; Risk Factors; Ultrasonography, Doppler, Duplex